Influence оf Dielectric Electrode Surface Coating on Discharge Gas Voltage at High Pressure - T. I. Shakhtakhtinski (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
It is shown that the reason of deviation from gas similarity law in the field of high pressure is the presence of microscopic protuberances on the electrode surface. Application of dielectric coating on the electrode surface does not eliminate an influence of microscopic protuberances on dis-charge gas voltage in the field of high pressure.